A Systematic Review of IoT-Enabled Predictive Drying for Arabica Coffee: Toward a Python-Based Digital Twin Framework for the Gayo Highlands, Aceh Tengah, Indonesia - Muhammad Ihsan; H. Susanto; Nuzuli Fitriadi (Jurnal Inotera, 2026)
Post-harvest drying is the single most decisive determinant of Arabica coffee quality, yet in the Gayo Highlands of Aceh Tengah (950 - 1,650 m.a.s.l.) it remains an experience based, weather dependent operation conducted largely on tarpaulins and open patios. High relative humidity, frequent rainfall, and low ambient temperature routinely prolong drying beyond ten days, produce non uniform final moisture content, and expose parchment to fungal colonisation and ochratoxin risk, causing smallholders to fail the 12.5% maximum moisture threshold of SNI 01-2907-2008 and to forfeit specialty price premiums. This systematic literature review, conducted following PRISMA guidelines on peer reviewed publications from 2019–2026, synthesises three research streams that have so far evolved in isolation: (i) thin layer drying kinetics of parchment coffee, (ii) Internet of Things (IoT) architectures for solar and hybrid dryers, and (iii) digital twin methodology in food and grain drying. The review finds that existing coffee drying IoT deployments are overwhelmingly reactive while validated kinetic models (modified Midilli, Page) capable of such prediction remain confined to laboratory dryers and are never coupled to field sensor streams. Digital twin research in drying has concentrated on grain and fruit, leaving coffee, and highland smallholder contexts in particular, unaddressed. From this synthesis the review derives seven research gaps and proposes SIKOPI-DT, a contextualised five layer Python based digital twin framework in which a modified Midilli kinetic core is continuously reparameterised by low cost IoT sensors (ESP32, SHT31, load cell) to forecast the time to target moisture content and to drive predictive supplementary-heat control under Gayo weather scenarios. Synthesised evidence indicates that such a system can plausibly reduce drying time by 30–50%, cut specific energy consumption by 15–30%, and improve moisture uniformity relative to open-sun practice. A three phase experimental validation roadmap and a smallholder economic feasibility analysis are presented, positioning this review as the theoretical foundation for a physical prototype in Aceh Tengah.